Optical spectroscopy study on the quality of used engine oil: article / Nor Nadiah Norzemi ... [et al.] - Norzemi, Nor Nadiah; Idros, M. F. M.; Noor, U. M.; Osman, F. N. (2010)
One of the current global concerns today is on the pollution happened to the environment caused by used engine oil. Some studies say that oil pollution caused twenty years for the environment to recover to its original condition and a gallon of oil can pollute a million gallons of fresh water [1]. Due to this dilemma, many researchers have been made in order to find the best way in minimizing the quantity of used engine oil disposed; hoping that by doing this can help in controlling the pollution done to the nature. This paper proposes a study using spectroscopic approach on the quality of engine oil where the aim is to find a way to reduce the waste of used engine. Optical spectroscopy concept is apply where percentage of reflectance intensity was measured using MCS600 ZEISS Spectrometer. The data was summarized by a line graph and was verified using statistic approach called Student tTest. The outcome can lead to a conclusion where the higher kilometer of the engine oil, the lower the intensity of light reflectance that will be obtained.